Electrical properties and morphology microscopy of palladium (Pd) Schottky contact on P-type GaN / C. K. Tan … [et al.] - Tan, C. K.; Yam, F. K.; Lim, C. W.; A., Abdul. Aziz; Z., Hassan (2004)
In this paper, we present the electrical, thermal, and morphological characteristics of Pd contacts to 'Mg-doped p-type GaN grown on sapphire substrate. Different annealing temperatures (300700°C) were investigated, as thermally stable metal-semiconductor contacts are essential for high quality devices. The barrier heights and leakage current of these contacts determined using current voltage (I-V) measurement were investigated. The surface morphology of the samples were assessed by Scanning Electron Microscopy (SEM) in which the change of structural property could significantly affect the performance of contacts. The experimental result revealed that the sample annealed at 400°C for 35 minutes was the optimum condition where the highest SBH (0.68 eV) with low leakage current (20 µA at -5V) was obtained.